Epidemiology of Ankle Sprain in the Active-Duty Military Population. Issue 6 (9th June 2022) - Goodrich, Ezra; Morris, Brandon; Hermanns, Christina; Herda, Ashley; Tarakemeh, Armin; Vopat, Bryan
Abstract : » Ankle sprain is one of the most prevalent injuries within the military population, resulting in health-care costs, time away from active duty, and negative impacts on overall readiness. » Female service members appear to be more likely to sustain ankle sprains than male service members. » There is a need for additional research on prevention methods and rehabilitation programs for ankle sprains in the military population because the rate of ankle sprain in this population exceeds that in populations with less physically demanding lifestyles. Consequently, low-cost prevention strategies could yield substantial benefits.